ARCUATE CRUSTAL STRUCTURES - Beloussov V.V. (My University, 1986)
The orogenic ridges on continents and island arcs have a similar history of development and character of tectonic deformations. They also have much in common with the linear ridges. The arcuate shape of orogenic uplifts is associated with long geological history, during which the consecutively appearing structures overlaid one another or inherited from one another. The shape of island arcs is presumably the result of their former geological development.